Influencing Mechanism of Shaoxing High School Parents' Purchase Intention in Selection of Online Courses - Hongwei Tu; Jacky Mong Kwan Watt (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The study investigates the influencing mechanisms behind Shaoxing High School parents' purchase intentions regarding online courses for their children's education. It identifies three primary factors: convenience, social influence, and performance expectations. Convenience pertains to the ease of access, flexibility, and user-friendliness of online platforms, significantly enhancing parents' willingness to enroll their children. Social influence highlights the impact of recommendations from peers and community members, reinforcing parents' confidence in their choices. Performance expectations focus on parents' beliefs about the educational outcomes of online courses, emphasizing the importance of perceived effectiveness and quality of instruction. These factors reveal a comprehensive framework that educational providers can leverage to tailor their offerings, thereby improving enrollment rates and student success in online learning environments. The findings underscore providers' need to address these key dimensions to enhance parental engagement and satisfaction in selecting educational programs based on the sample population of 380 high school parents.